Parasite-Induced Chronic Inflammation Is Not Exacerbated by Immunotherapy before or during Trypanosoma cruzi Infection - Duthie, Malcolm S. (American Society for Microbiology, 2007)
Trypanosoma cruzi infection causes Chagas' disease, a chronic inflammatory disease. The specific inflammatory responses that cause Chagas' disease remain unclear, but data argue that parasites that persist in the host stimulate chronic self-damaging immune responses. Because T. cruzi appears to stimulate self-damaging responses, the enthusiasm to develop vaccines that boost antiparasite responses that might increase self-damaging responses has been limited. We previously demonstrated that immunization with a T. cruzi trans-sialidase protein or adoptive transfer of trans-sialidase-specific T-cell clones decreased parasitemia, morbidity, and mortality. Here we report that immunization or adoptive transfer with the protein or clones, before or during T. cruzi infection, boosts the anti-T. cruzi immune response without exacerbating acute or chronic tissue inflammation. These results argue that prophylactic and therapeutic immunotherapy for Chagas' disease can be developed safely.